MONITORING OF INDUSTRIAL ENERGY CONSUMPTION AND INCREASING ENERGY EFFICIENCY - Saydaliyeva Dilorom Nimadovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article given information on how to economize energy resources and the growth in energy supply in Uzbekistan